Peran dan Kompetensi Juru Sembelih Halal (JULEHA) Perspektif Hukum Islam (TAWAZUN: Journal of Sharia Economic Law, 2023)
Slaughtering an animal in Islamic law is a way to get rid of the animal's soul by cutting the neck, esophagus and throat as well as the two arteries with a sharp instrument or other methods justified by Islamic law. Because the meat of slaughtered animals must be halal in the process as well. To realize the halal way of slaughtering, it is necessary to have education in the form of socialization and training by Halal Slaughtering Experts. The role of this expert is very important to make this happen. In this study, the researcher aims to find out the role of the Halal Slaughterperson (JULEHA) in Maintaining the Halal Slaughter Meat and the Competence of the Halal Slaughterperson from the Perspective of Islamic Law. The results of this study show that the Halal Slaughterer plays a very important role in maintaining the halalness of Slaughtered Meat by providing education, outreach, training and the practice of Slaughtering that is syar'i. This affects the blessings in the economy according to sharia.